RANCANG BANGUN SISTEM INFORMASI PERALATAN PERNIKAHAN BERBASIS WEB STUDI KASUS CV. GAMALAMA WONOKROMO (DESIGN INFORMATION SISTEMS FOR EQUIPMENT WEDDING WITH BASED WEB CASE STUDY IN CV. GAMALAMA WONOKROMO) - Rahman Prehanto, Dedy; Kartika Cahyani, Dessy (Inovate, 2016)
Technological developments can affect many aspects, including the economy, politics, government, andmany others. This influence makes many changes in lifestyle and the way people are used to and are inthe technological environment. They want to be facilitated in every way, one of them in the tradingbusiness, they do not want to waste time and effort in selecting the items they want. This makes a lot of trading business leasing, selling or renting their goods over the internet, world trade is no longer limitedby space and time. High mobility of people demanding world trade is able to provide services and goodswith instant according to consumer demand. The method used in completing this information Sistem is the Research and Development (R & D) thefirst step on the author is collecting literature from textbooks, magazines and the Internet on anyinformation required in the manufacture of Design of Information Sistems Equipment Marriage-BasedWeb and then apply in the manufacture of Information Sistems. The result of this research is a Web-based information Sistem that can help or easier for companies todevelop business in a broader scope. In addition, consumers can obtain information and reservations about the marriage of equipment in the web. Keyword: Web, Information Sistems, Wedding